2020
DOI: 10.3389/fpubh.2020.00206
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Early-Stage Clinical Features Between COVID-19 and Influenza A H1N1 Virus Pneumonia

Abstract: Introduction: Influenza virus pneumonia and COVID-19 are two different types of respiratory viral pneumonia but with very similar clinical manifestations. The aim of the present study was to help clinicians gain a better understanding about differences between Influenza virus pneumonia and COVID-19 by comparative analysis of the early-stage clinical features. Methods: Clinical data of patients with confirmed diagnosis of COVID-19 and influenza A pneumonia identified in our hospital were collected and analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 20 publications
1
27
0
2
Order By: Relevance
“…Severe cases are prone to various complications and may further increase the chance of human death [ 9 , 10 ]. Shen et al [ 11 ] suggested that patients with COVID-19 were more likely to progress within 1 week. The early definition of COVID-19 was defined as within 7 days of clinical symptoms, and within 7 days of positive viral nucleic acid test for asymptomatic patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Severe cases are prone to various complications and may further increase the chance of human death [ 9 , 10 ]. Shen et al [ 11 ] suggested that patients with COVID-19 were more likely to progress within 1 week. The early definition of COVID-19 was defined as within 7 days of clinical symptoms, and within 7 days of positive viral nucleic acid test for asymptomatic patients [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…influenza virus has its own typical hematological features of leukopenia, relative lymphopenia with rare thrombocytopenia. [18,19] LIMITATIONS This is a very narrow literature review as we just focused on performing a brief comparison of those aspects of the 2 pandemics that were scientifically proven.…”
Section: And Discussionmentioning
confidence: 99%
“…The results for of all pairwise group comparisons are provided as supplementary Table S2. For each variable and compared pair, the table provides the time gap for which the stronger difference in rank means slopes was found, either (0-6, 6-24) or (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and the difference itself. Figure 4 represents the trends for each of the variables showing a significant effect on diseases trajectories.…”
Section: Demographics As Shown Inmentioning
confidence: 99%